TYPES OF AUTONOMOUS LAW AND UNDERSTANDING OF LEGAL PLURALISM - Vukadinović, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Resume: Just as there isn’t a generally accepted meaning of the term law, there still isn’t a completely clear and defined meaning of the term autonomous law. There is a big interest for the autonomous law in practice and theory, sociology and law anthropology. Five main meanings are attributed to this term: autonomous law as a theoretic notion, a subsystem of law, source of law, law of work and autonomous identity law. When it comes to autonomous law as a theoretic notion it is closely linked with the idea of legal pluralism. This paper follows the development of the understanding of legal pluralism from Duguit, Ehrlich, Petrazycki, Gurvitch, through, Evan, Llewellyn, Hobel, to Vanderlinden and Jean-Guy Belley. The paper ends with ’a new legal pluralism’ which has a tendency to become the only right school (legal orthodoxy).